Road Transport Improvements and Network Congestion. - Venables, A (1999)
This article considers the welfare effects of road transport improvements in a congested network, and shows how an improvement can be welfare reducing if it creates congestion on other parts of the network. Conditions for welfare gain or loss are found, and it is shown that a welfare loss is likely if the improvement benefits short journeys sharing a congested road with longer journeys.